Kerangka Teologis Islamic Social Finance untuk Mendukung Sustainable Development Goals (SDGs): Studi atas QS. At-Taubah: 60 dan QS. Al-Baqarah: 267 - Muhammad Zainudin; Muhammad Ibnu Akbar Nuryadi; Ahmad Djalaluddin (Pustaka Peradaban, 2026)
This study aims to formulate a theological-functional framework of Islamic Social Finance (ISF) in supporting the Sustainable Development Goals (SDGs) through a Tafsir Maudu’i (thematic exegesis) approach to Surah At-Taubah: 60 and Surah Al-Baqarah: 267. This qualitative research identifies and synthesizes the normative principles of the Qur'an to bridge the gap between the potential of Islamic philanthropic resources and the financing needs of sustainable development. The key findings indicate that two normative pillars of the Qur'an provide an explicit mandate for this integration. The Distribution Structure Pillar (QS. At-Taubah: 60) transforms Zakat into a productive empowerment instrument that directly supports SDG 1 (No Poverty) and SDG 4 (Quality Education). The Financing Quality Pillar (QS. Al-Baqarah: 267) provides ethical and managerial justification for long-term investment through Waqf and Infaq, directed toward sustainable infrastructure funding, transparent governance, and environmental issues (SDGs 3, 7, 13, 16). Philosophically, this integration demonstrates the alignment of Maqasid Syariah with universal development goals. The study concludes that ISF has significant potential to be a stable, directed, and ethical driving force in achieving the 2030 Sustainable Development Agenda. The institutional transformation of ISF, through the adoption of dual performance indicators (Sharia metrics and SDG impact metrics), is key to ensuring that ZISWAF funds generate measurable social and environmental impacts. Penelitian ini bertujuan merumuskan kerangka teologis-fungsional Islamic Social Finance (ISF) dalam mendukung Sustainable Development Goals (SDGs) melalui pendekatan Tafsir Maudu’i terhadap QS. At-Taubah: 60 dan QS. Al-Baqarah: 267. Penelitian kualitatif ini mengidentifikasi dan mensintesis prinsip-prinsip normatif Al-Qur’an untuk mengatasi kesenjangan antara potensi sumber daya filantropi Islam dan kebutuhan pendanaan pembangunan berkelanjutan. Temuan kunci menunjukkan bahwa dua pilar normatif Al-Qur’an menyediakan mandat eksplisit untuk integrasi ini. Pilar Struktur Distribusi (QS. At-Taubah: 60) mentransformasi Zakat menjadi instrumen pemberdayaan produktif yang secara langsung mendukung target SDG 1 (Tanpa Kemiskinan) dan SDG 4 (Pendidikan). Pilar Kualitas Pendanaan (QS. Al-Baqarah: 267) memberikan justifikasi etis dan manajerial bagi investasi jangka panjang melalui Wakaf dan Infak, yang diarahkan untuk pendanaan infrastruktur berkelanjutan, tata kelola transparan, dan isu lingkungan (SDG 3, 7, 13, 16). Secara filosofis, integrasi ini menunjukkan keselarasan Maqasid Syariah dengan tujuan pembangunan universal. Penelitian menyimpulkan bahwa ISF memiliki potensi besar untuk menjadi kekuatan pendorong yang stabil dan etis dalam mencapai Agenda Pembangunan Berkelanjutan 2030. Transformasi kelembagaan ISF, melalui adopsi indikator kinerja ganda (Syariah dan metrik dampak SDGs), adalah kunci untuk memastikan dana ZISWAF menghasilkan dampak sosial dan lingkungan yang terukur.